Talkability : discover the secrets of effective conversation - Borg, James (Pearson, 2016)
A new book from James Borg - on what to say and how to say it - so you can get more from the way you talk. All the day-to-day conversations that you have in your private and working life result in a particular outcome. How many times do you come away from a situation and think you could have handled it better? The realization that you should have used different words or said things in a different tone which might have produced a more positive result or avoided friction. How often have you felt frustrated at your inability to state your case and to explain your thoughts well enough for the ot.